S̆koda-artillery of the Liebknecht-battery captured in the battle of Guadalajara in fire-position. Copied from collection Museum für Deutsche Geschichte (1937)
S̆koda-artillery of the Liebknecht-battery captured in the battle of Guadalajara in fire-position. Copied from collection Museum für Deutsche Geschichte.